Complementary Role of Oxytocin and Vasopressin in Cardiovascular Regulation - Ewa Szczepanska-Sadowska (MDPI AG, 2021)
The neurons secreting oxytocin (OXY) and vasopressin (AVP) are located mainly in the supraoptic, paraventricular, and suprachiasmatic nucleus of the brain. Oxytocinergic and vasopressinergic projections reach several regions of the brain and the spinal cord. Both peptides are released from axons, soma, and dendrites and modulate the excitability of other neuroregulatory pathways. The synthesis and action of OXY and AVP in the peripheral organs (eye, heart, gastrointestinal system) is being investigated. The secretion of OXY and AVP is influenced by changes in body fluid osmolality, blood volume, blood pressure, hypoxia, and stress. Vasopressin interacts with three subtypes of receptors: V1aR, V1bR, and V2R whereas oxytocin activates its own OXTR and V1aR receptors. AVP and OXY receptors are present in several regions of the brain (cortex, hypothalamus, pons, medulla, and cerebellum) and in the peripheral organs (heart, lungs, carotid bodies, kidneys, adrenal glands, pancreas, gastrointestinal tract, ovaries, uterus, thymus). Hypertension, myocardial infarction, and coexisting factors, such as pain and stress, have a significant impact on the secretion of oxytocin and vasopressin and on the expression of their receptors. The inappropriate regulation of oxytocin and vasopressin secretion during ischemia, hypoxia/hypercapnia, inflammation, pain, and stress may play a significant role in the pathogenesis of cardiovascular diseases.